The Science of Happiness: How our brains make us happy--and what we can do to get happier - Stefan Klein (Marlowe, 2006)
Draws on the latest findings in neuroscience and neuropsychology to explain the biological purpose and feasibility of happiness, in an account that offers insight into the motivational factors behind the pursuit of happiness and the conditions that are required to achieve it.